Vacancy growth in crystals - Ng, Jerome Shao Zhee. (2010)
Free energy is the driving force behind many phenomenons in nature. In this study, the proposed -1 method for predicting free energy in perfect crystals and monovacancy systems was evaluated. The average distance between the particle of interest and its nearest neighbors was first measured. This distance was then used to approximate the accessible volume of the particle using a sphere and a Wigner-Seitz cell. This approximated volume was used to determine the particle’s free energy. This -1 method provided free energy values close to the theoretical free energy values for perfect crystal systems with Face Centered Cubic (FCC), Hexagonal Closed Pack (HCP) and Body Centered Cubic (BCC) structures. In addition, it was discovered that the approximation of the accessible volume to a sphere worked better for the FCC and HCP crystal structure system while the approximation to a Wigner-Seitz cell worked better for a BCC crystal structure system. Subsequently, this method was applied to a monovacancy system with a FCC and a HCP structure. However, it did not provide acceptable results for monovacancy systems.